An Interview with APPLE Lecture Speaker Dr. Okim Kang - Daniel Eskin; Soo Joo; Kelly Katherine Frantz (Studies in Applied Linguistics & TESOL, 2025)
On April 18th, 2025, the Studies in Applied Linguistics and TESOL (SALT) journal interviewed Dr. Okim Kang, an invited speaker for the 2025 APPLE Lecture Series hosted by the Applied Linguistics and TESOL program at Teachers College, Columbia University.